2021
DOI: 10.3390/ijms22158348
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Size Control of Efficient and Safe Nanopesticides by Anodic Aluminum Oxide Templates-Assisted Method

Abstract: Efficient and safe nanopesticides play an important role in pest control due to enhancing target efficiency and reducing undesirable side effects, which has become a hot spot in pesticide formulation research. However, the preparation methods of nanopesticides are facing critical challenges including low productivity, uneven particle size and batch differences. Here, we successfully developed a novel, versatile and tunable strategy for preparing buprofezin nanoparticles with tunable size via anodic aluminum ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The results are in conformity with the earlier findings (Bolan et al, 1991; Keren & Shainberg, 1981). As per the Noyes–Whitney equation, the total effective surface area of particles gets increased when particle size is reduced, which results in an enhanced dissolution rate (Wang et al, 2021). Moreover, particle size reduction reduces the thickness of the diffusion layer surrounding MG particle and increases the concentration gradient.…”
Section: Discussionmentioning
confidence: 99%
“…The results are in conformity with the earlier findings (Bolan et al, 1991; Keren & Shainberg, 1981). As per the Noyes–Whitney equation, the total effective surface area of particles gets increased when particle size is reduced, which results in an enhanced dissolution rate (Wang et al, 2021). Moreover, particle size reduction reduces the thickness of the diffusion layer surrounding MG particle and increases the concentration gradient.…”
Section: Discussionmentioning
confidence: 99%
“…The size and shape of the sample particle are directly determined by the hard template, which is a rigid material with a fixed structure. By using a cooperative assembly between the surfactant and inorganic species, the hard-template approach is an effective way to create Mesoporous materials that are challenging to synthesize by conventional methods [33]. The idea is extremely straightforward and was first put forward by Ryoo et al and Hyeon and coworkers.…”
Section: Hard Templatementioning
confidence: 99%
“…Especially in many synthetic processes and in several natural processes, biopolymers as well as their colloids can serve as templates and regulating agents [83]. The idea of employing biological substances as soft templates is quite intriguing, and a great deal of work has been done to use biological materials with regulated properties that are easily obtainable and economically priced.…”
Section: Biopolymermentioning
confidence: 99%
“…The other encompasses green pesticide formulations, such as water emulsions (EWs), water-suspending agents (SCs), microemulsions (MEs), suspension emulsions (SEs), and water-dispersible granules (WDGs) [ 2 ]. However, some pesticide formulations have limitations such as a large particle size, low effective utilization rate, poor dispersion, and inconvenient transportation for practical applications [ 3 , 4 , 5 ]. Studies in recent years have shown that 90% of pesticides are not used effectively in the application process, posing a threat to the environment, and increasing application costs for farmers [ 6 ].…”
Section: Introductionmentioning
confidence: 99%